Pengaruh Kekuatan Balok Induk Terhadap Dimensi Balok Anak Pada Beton Bertulang - Tahan Tahan (Media Ilmiah Teknik Sipil, 2019)
Generally, concrete can be categorized into normal quality concrete and high-quality concrete, both are commonly used in construction. Normal quality concrete has approximately 20 MPa to 58 MPa quality, while the high-quality concrete has higher than 58 MPa. One of the applications of these concrete in structure is the dimension and joist position toward the beam’s strength in a story structure. To analyze the effect of joist toward beam, Finite Element Analysis (FEA)is applied with the following: Utilizing ANSYS with SOLID65, SOLID45, LINK8 with varying size of joist and beam such as type A beam by the size of 30/40 and joist by the size of 20/40, 25/40, 30/40, type B beam by the size of 30/50 and joist size of 25/50, 25/40, 25/35 and type C beam by the size of 40/60 and the joist size of 35/60, 35/50, 35/40. Steel material is used each has 400 MPa for the main reinforcement tension, 200 MPa for the stirrup reinforcement, normal quality concrete tension of 25 MPa, placement tension of 400 MPa, steel modulus elasticity of 200,000 MPa. Based on the FEA it is obtained that the comparison of joist influence toward the beam is centered from the comparison result of